2011
DOI: 10.1523/jneurosci.2266-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Little Exercise, Big Effects: Reversing Aging and Infection-Induced Memory Deficits, and Underlying Processes

Abstract: We have previously found that healthy aged rats are more likely to suffer profound memory impairments following a severe bacterial infection than are younger adult rats. Such a peripheral challenge is capable of producing a neuroinflammatory response, and in the aged brain this response is exaggerated and prolonged. Normal aging primes, or sensitizes microglia and this appears to be the source of this amplified inflammatory response. Among the outcomes of this exaggerated neuroinflammatory response are impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 43 publications
8
131
0
1
Order By: Relevance
“…Importantly, exercise effectively countered the naturally occurring age-related decline in CX 3 CL1 levels within the hippocampus of aged mice, restoring them to those seen in young animals. These findings are supported by a recent study by Barrientos et al (2011), who suggested a potential beneficial link between running and altered neuroinflammatory responses. In our study, direct evidence for a role of CX 3 CL1 in regulating NPC activity was demonstrated via intraparenchymal infusion of a CX 3 CR1 blocking antibody into the hippocampus, which largely abolished the positive effect that microglia normally exert on these cells during running.…”
Section: Role Of Microglia In Neural Precursor Activationsupporting
confidence: 85%
“…Importantly, exercise effectively countered the naturally occurring age-related decline in CX 3 CL1 levels within the hippocampus of aged mice, restoring them to those seen in young animals. These findings are supported by a recent study by Barrientos et al (2011), who suggested a potential beneficial link between running and altered neuroinflammatory responses. In our study, direct evidence for a role of CX 3 CL1 in regulating NPC activity was demonstrated via intraparenchymal infusion of a CX 3 CR1 blocking antibody into the hippocampus, which largely abolished the positive effect that microglia normally exert on these cells during running.…”
Section: Role Of Microglia In Neural Precursor Activationsupporting
confidence: 85%
“…Given that, BDNF is required for consolidation of hippocampal-dependent memory (Alonso et al 2002a, b;Tyler et al 2002), a reduction in this plasticityrelated molecule could be critical for the hippocampal-dependent memory disturbances produced by US. And finally, although the mechanisms for stressorand pathogen-evoked cytokine release are not interchangeable (Campeau et al 2010;Campisi et al 2012;Maslanik et al 2012), it is interesting to note that wheel running was recently reported to reduce hippocampal microglia activation, brain proinflammatory cytokine responses, and BDNF reductions after peripheral bacterial challenge in older rats (Barrientos et al 2011) lending additional support to our hypothesis that regular physical activity may quiet stressor-evoked hippocampal microglia activation, and protect against BDNF down-regulation and reduced neurogenesis.…”
Section: Mechanisms For Stress Robustness Produced By Physicalmentioning
confidence: 65%
“…Hence, the present findings suggested that the exercise before, after, and during stress could keep the balance of hippocampal IL-1 β level in the stress conditions. Conversely, Barrientos et al reported that exercise had no effect on the basal hippocampal IL-1β level (44).…”
Section: Discussionmentioning
confidence: 96%
“…Some studies reported that stress increased the central IL-1β level (43,44). On the other hand, it was also demonstrated that IL-1β is an important neurochemical mediator in the stress-induced stimulation of the hypothalamicpituitary-adrenal (HPA) axis and the secretion of adrenocorticotropin (ACTH) and corticosterone (CORT) (45,46).…”
Section: Discussionmentioning
confidence: 99%